ANALYSIS OF THE EFFECT OF WATER SALINITY ON THE IMPRESSED CURRENT CATHODIC PROTECTION PHOTOVOLTAIC (ICCP PV) SYSTEM - Budiarto, Untung; Samuel, Samuel; Yunior, Tri Rangga; Frestiqauli, Santi; Ahmad, Syaiful Tambah Putra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Cathodic protection is one of the methods used to protect metals from corrosion. This corrosion can occur due to the influence of the surrounding environment, such as salinity levels. ICCP PV is a cathodic protection method by flows direct electric current from the conversion of solar radiation. The purpose of this study is to determine the effect of water salinity on the capacity of PV components in the ICCP system. The type of material used in this research is SS 400 steel with salinity variations of 0‰, 30‰, and 35‰. The tests carried out are salinity test and load power test by considering metal potential. The experimental results show that 35‰ salinity ICCP requires the highest power of 13.09 watts. Calculation of PV component capacity at 35‰ salinity ICCP requires the largest capacity, which is 170 Wp PV module and 75 Ah battery for 14.68 m² plate area. Based on this, it is concluded that the higher the salinity of water, the greater the power required for the ICCP system, thus affecting the capacity of PV components for the ICCP system.